The Role of Internal Auditing in Upholding Corporate Governance Standards - Pangastuti, Leli Agustina (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This research explores the internal audit's multifaceted role in maintaining corporate governance standards, focusing on internal audit's contribution to organizational transparency, accountability, and integrity. Research Design and Methodology: This research uses a comprehensive literature review approach, systematically identifying and synthesizing scholarly works, theoretical frameworks, and empirical studies related to internal audit and corporate governance. Findings and Discussion: The results emphasize the importance of the internal audit function in improving organizational transparency, accountability, and integrity through independent assessment of internal control systems, risk management, and regulatory compliance. Implications: This research's implication is to provide practical guidance for organizations in improving governance and risk management. It emphasizes the importance of investing in internal audit, establishing a culture of transparency and accountability, and adopting innovative technologies such as artificial intelligence and machine learning in the audit process.